Deductive, inductive and abductive reasoning: diferences amd Integration from business examples - Galdo Jiménez, Alfredo José (2021)
This article merges in a creative manner the logic theory of argumentation and the business world. The aim of the essay is to propose several differentiating criteria between deductive and inductive reasoning thinking and to explain how abductive reasoning works in the argumentative process through the presentation of deliberate examples that allow the reader a greater understanding of the argumentation of ideas de field of logic.